Involvement of microRNA Lethal-7a in the Regulation of Embryo Implantation in Mice - Liu, Wei-Min (Public Library of Science, 2012)
MicroRNAs interact with multiple mRNAs resulting in their degradation and/or translational repression. This report used the delayed implantation model to determine the role of miRNAs in blastocysts. Dormant blastocysts in delayed implanting mice were activated by estradiol. Differential expression of 45 out of 238 miRNAs examined was found between the dormant and the activated blastocysts. Five of the nine members of the microRNA lethal-7 (let-7) family were down-regulated after activation. Human blastocysts also had a low expression of let-7 family. Forced-expression of a family member, let-7a in mouse blastocysts decreased the number of implantation sites (let-7a: 1.1±0.4; control: 3.8±0.4) in vivo, and reduced the percentages of blastocyst that attached (let-7a: 42.0±8.3%; control: 79.0±5.1%) and spreaded (let-7a: 33.5±2.9%; control: 67.3±3.8%) on fibronectin in vitro. Integrin-β3, a known implantation-related molecule, was demonstrated to be a target of let-7a by 3′-untranslated region reporter assay in cervical cancer cells HeLa, and Western blotting in mouse blastocysts. The inhibitory effect of forced-expression of let-7a on blastocyst attachment and outgrowth was partially nullified in vitro and in vivo by forced-expression of integrin-β3. This study provides the first direct evidence that let-7a is involved in regulating the implantation process partly via modulation of the expression of integrin-β3. (200 words).